Metal-Free Pyrene-Based Conjugated Microporous Polymer Catalyst Bearing N- and S-Sites for Photoelectrochemical Oxygen Evolution Reaction - Das, Sabuj Kanti; Shyamal, Sanjib; Das, Manisha; Mondal, Saptarsi; Chowdhury, Avik; Chakraborty, Debabrata; Dey, Ramendra Sundar; Bhaumik, Asim (Frontiers in Chemistry, 2021)
The development of an efficient, sustainable and inexpensive metal-free catalyst for oxygen evolution reaction (OER) via photoelectrochemical water splitting is very demanding for the energy conversion devices like green fuel generators, fuel cells and metal-air batteries. Herein, we have developed a metal-free pyrene-based nitrogen and sulphur containing conjugated microporous polymer having high BET surface area (761 m2 g-1) and low band gap of 2.09 eV for OER from alkaline solution. The π-conjugated as synthesized porous organic material (PBTDZ) has been characterized by Fourier transform infrared spectroscopy (FT-IR), solid state 13C (cross-polarization magic angle spinning-nuclear magnetic resonance) CP-MAS NMR, N2 adsorption/desorption analysis, field-emission scanning electron microscope (FESEM), high resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS) and thermogravimetric analysis (TGA) experiments. The material acts as an efficient catalyst for photoelectrochemical OER with a current density of 80 mA/cm2 at 0.8 V vs Ag/AgCl and delivered 104 mmol of oxygen in 2 h run. The presence of low band gap energy, π-conjugated conducting polymeric skeleton bearing donor heteroatoms (N and S), and higher specific surface area associated with inherent microporosity are responsible for this admirable photoelectrocatalytic activity of PBTDZ catalyst.